Therapeutic Effect of Upper Limb Intelligent Rehabilitation Robot and Routine Rehabilitation Combination on Upper Extremities'Motor Function of Stroke Patients - Dongyan XU; Rujin TIAN; Jue LIU; Gang LIU; Yulian ZHU (康复学报)
Objective:To observe the therapeutic effect of upper limb intelligent rehabilitation robot and routine rehabilitation combination on upper extremities'motor function of stroke patients.Methods:30 stroke patients accorded with inclusive criteria were selected, all patients received routine rehabilitation for two weeds, each time for twenty minutes, once a day and five days each week. The Fugl-Meyer assessment upper extremities (FMA-UE), modified Barthel index (MBI) and Brunnstrom score (upper extremities and hands) were used to evaluate upper extremities'motor function before the treatment and after ten times of treatment. After the evaluation, all patients received upper limb intelligent rehabilitation robot and routine rehabilitation for four weeks, each time for twenty minutes, once a day and five days each week. The system training score, FMA-UE, MBI and Brunnstrom score were used to evaluate upper extremities'motor function before the treatment, after ten times of treatment and after twenty times of treatment.Results:FMA-UE score of patients was increased after ten times of routine rehabilitation compared with that before treatment (P<0.05). System training score, FMAUE score, MBI and Brunnstrom score (hands) of patients were increased after ten times of upper limb intelligent rehabilitation robot and routine rehabilitation compared with those before treatment (P<0.05). System training score, FMA-UE score, MBI and Brunnstrom score (upper extremities and hands) of patients were increased after twenty times of upper limb intelligent rehabilitation robot and routine rehabilitation compared with those before treatment (P<0.05). System training score, FMA-UE score, MBI and Brunnstrom score (upper extremities and hands) of patients were increased after twenty times of upper limb intelligent rehabilitation robot and routine rehabilitation compared with those after ten times of upper limb intelligent rehabilitation robot and routine rehabilitation (P<0.05).Conclusion:Upper limb intelligent rehabilitation robot and routine rehabilitation may facilitate the recovery of upper extremities'motor function of stroke patients, and the method is worthy of clinical spreading application.